Destructive methods in uterine bleeding outpatient treatment - Basta, Antoni; Jach, Robert; Basta, Paweł; Ludwin, Artur (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction of the ablation, in the 1980s, as a new technique of conservative management of metrorrhagia due to endometrial hyperplasia has significantly decreased the percentage of hysterectomies and is gaining more attention. Endometrial ablation with the use of hysteroscopy refers to three methods of endometrial removal, which are defined as the first generation techniques. This group comprises transcervical endometrial resection, endometrial destruction with the revolving electrode and the laser endometrial destruction. Based on our own hysteroscopic endometrial ablation material, which comprises 876 cases of hysteroscopic endometrial resection and 51 cases of endometrial destruction by the revolving electrode, our observations, experience and the efficacy of these procedures have been discussed. In the 1990s new methods using different types of energy for endometrial destruction, known as the second generation techniques, were introduced. This group consists of thermal intracavitary balloons (ThermaChoice System), hydro-thermic method (Hydrotherm System), multielectrode balloon system, microwave method, endometrial cryoablation and endometrial intrauterine laser therapy. These methods may be used provided that endometrial atypia had been excluded and a regular follow-up is possible. The most common method of endometrial ablation is one of the second generation techniques: ThermaChoice System. Although hysteroscopic endometrial resection is the most efficient method, the destructive methods are less invasive, easier to perform and involve fewer complications.